2000
DOI: 10.1016/s0092-8674(00)80877-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin Expressed in Nonneuronal Cells Triggers Presynaptic Development in Contacting Axons

Abstract: Most neurons form synapses exclusively with other neurons, but little is known about the molecular mechanisms mediating synaptogenesis in the central nervous system. Using an in vitro system, we demonstrate that neuroligin-1 and -2, postsynaptically localized proteins, can trigger the de novo formation of presynaptic structure. Nonneuronal cells engineered to express neuroligins induce morphological and functional presynaptic differentiation in contacting axons. This activity can be inhibited by addition of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

49
1,084
5
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,105 publications
(1,143 citation statements)
references
References 42 publications
49
1,084
5
5
Order By: Relevance
“…The postsynaptic Nlgns form heterophilic connections with Nrxns and are thus important for synapse formation and cognitive functions (Dean and Dresbach 2006). These proteins even induce the differentiation of presynaptic and postsynaptic specialization respectively in adjoining nonneuronal cells (Scheiffele et al 2000;Graf et al 2004). Moreover, their interaction is involved in neuronal plasticity mechanism and neuronal disorders such as autism (Südhof 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The postsynaptic Nlgns form heterophilic connections with Nrxns and are thus important for synapse formation and cognitive functions (Dean and Dresbach 2006). These proteins even induce the differentiation of presynaptic and postsynaptic specialization respectively in adjoining nonneuronal cells (Scheiffele et al 2000;Graf et al 2004). Moreover, their interaction is involved in neuronal plasticity mechanism and neuronal disorders such as autism (Südhof 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the former possibility, however, it has been shown that postsynaptic proteins can induce presynaptic assembly and drive the formation of new presynaptic contacts (Biederer et al, 2002;Scheiffele et al, 2000). Furthermore, the postsynaptic scaffolding protein PSD95, along with its interaction partners, can modulate the release probability of presynaptic transmitter vesicles in a retrograde manner (Futai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although different works suggested their involvement in synapses formation (Scheiffele et al, 2000;Dean et al, 2003;Graf et al, 2004;Prange et al, 2004;Chubykin et al, 2005;Levinson et al, 2005), other studies and the analysis of knockout mice proposed that Neuroligins, along with the alphaforms of Neurexins, are involved in synaptic function and maturation (Missler et al, 2003;Sara et al, 2005;Varoqueaux et al, 2006;Chubykin et al, 2007). Triple knockout mice lacking Nlgn1-3 die shortly after birth and present normal synapse numbers with an apparently normal ultrastructure (Varoqueaux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%